A Day in the Life of MRI: The Variety and Appropriateness of Exams Being Performed in Canada. Issue 2 (May 2018) - Vanderby, Sonia; Badea, Andreea; Peña Sánchez, Juan Nicolás; Kalra, Neil; Babyn, Paul
Purpose: This study aimed to determine the volumes and types of magnetic resonance imaging exams being performed across Canada, common indications for the exams, and exam appropriateness using multiple evaluation tools. Methods: Thirteen academic medical institutions across Canada participated. Data were obtained relating to a single common day, October 1, 2014. Patient demographics, type by anatomic region and indication for imaging were analysed. Each exam was assessed for appropriateness via the Canadian Association of Radiologists Referral Guidelines and the American College of Radiology Appropriateness Criteria. The Alberta and Saskatchewan spine screening forms and the Alberta knee screening form were also used where applicable. The proportion of exams that were unscorable, appropriate, and inappropriate was determined. Exam-level results were compared between the 2 main evaluation tools. Results: Data were obtained for 1087 relevant exams. There were 591 women and 460 men. 36 requisitions did not indicate the patient's sex. Brain exams were the most common, comprising 32.5% of the sample. Cancer was the most common indication. Overall, 87.0%–87.4% of the MR exams performed were appropriate; 6.6%–12.6% were inappropriate, based on the 2 main evaluation tools. Results differed by anatomic region; spine exams had the highest proportion, with nearly one-third of exams deemed inappropriate. Conclusion: Variations by anatomic region indicate that focused exam request evaluation or screening methods could substantially reduce inappropriate imaging.